Vitamin E and the Healing of Bone Fracture: The Current State of Evidence. (9th December 2012) - Borhanuddin, Boekhtiar; Mohd Fozi, Nur Farhana; Naina Mohamed, Isa
Abstract : Background. The effect of vitamin E on health-related conditions has been extensively researched, with varied results. However, to date, there was no published review of the effect of vitamin E on bone fracture healing. Purpose. This paper systematically audited past studies of the effect of vitamin E on bone fracture healing. Methods. Related articles were identified from Medline, CINAHL, and Scopus databases. Screenings were performed based on the criteria that the study must be an original study that investigated the independent effect of vitamin E on bone fracture healing. Data were extracted using standardised forms, followed by evaluation of quality of reporting using ARRIVE Guidelines, plus recalculation procedure for the effect size and statistical power of the results. Results. Six animal studies fulfilled the selection criteria. The study methods were heterogeneous with mediocre reporting quality and focused on the antioxidant-related mechanism of vitamin E. The metasynthesis showed α -tocopherol may have a significant effect on bone formation during the normal bone remodeling phase of secondary bone healing. Conclusion. In general, the effect of vitamin E on bone fracture healing remained inconclusive due to the small number of heterogeneous and mediocre studies included in this paper.